PENGEMBANGAN UBI JALAR BERBASIS PENGELOLAAN LIMBAH ORGANIK DI KOTA PADANG - PK Dewi Hayati; Sutoyo Sutoyo; Teguh Budi Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
Sweet potato cultivation has potential to support the home industry in Padang city. Theaims of this community service program were to transfer knowledge and technology inmanagement of organic waste from household and farmer field, to applied the organic fertilizerin sweet potato cultivation, and to increase the value added of sweeet potato tuber. The programwas conducted from March to October 2015 in Ikur Koto, Koto Tangah District, Padang, WestSumatra. The partners were the Kelompok Wanita Tani (KWT) Pagai and Kelompok Tani danTernak Parak Tanjung Jaya. The methods of technology transfer were socialization anddiscussion, training, demplot or demonstration plot and demonstration in creating severalproducts from sweet potato tuber. The outcomes obtained in the end of the program are theability of communities to produce organic fertilizers and biopesticide. The farmers are successto applied the organic fertilizer to substitute 25% synthetic fertilizer, and able to produceseveral products from sweet potato tuber.